Access and benefit sharing in participatory plant breeding in Southwest China - Song. Y.; Zhang, Y.; Song, X.; Vernooy, Ronnie (Centre for Learning on Sustainable Agriculture (ILEIA), 2016)
This article discusses access and benefit sharing within the context of participatory plant breeding. It presents how Chinese farmers and breeders collaborate in relation to crop improvement and on-farm maintenance of plant genetic resources. Based on more than a decade of action-research, a number of institutional changes were accomplished as a result of the interactions between national and provincial breeding institutes, rural development researchers and local maize farmers. Although the respective legislation in China is not yet adequately formulated, access and benefit sharing can still be addressed in contracts and by labelling products of a particular geographic origin.